Physiotherapy Management of Frozen Shoulder Dextra with InfraRed (IR), Transcutaneous Electrical Nerve Stimulation (TENS) and Active Exercise Modalities - Kriatiawan, Ardianus Jefri; Purnomo, Didik (Jurnal Indonesia Sosial Sains, 2024)
Frozen shoulder, commonly called adhesive capsulitis, is a painful condition in the shoulder and results in a limited range of motion of the joint (LGS). Frozen shoulder is a condition where shoulder movement becomes limited. Frozen shoulder has varying degrees of severity, ranging from mild to severe pain, and the degree of limitation to movement of the glenohumeral joint. To reduce pain and limited joint movement, which will later increase the ability for functional activities, the role and modalities of physiotherapy can be used in the form of InfraRed, Transcutaneous Electrical Nerve Stimulation, and Active Exercise. This scientific paper is a case study that raises patient cases and collects data through physiotherapy. InfraRed, Transcutaneous Electrical Nerve Stimulation, and Active Exercise are the modalities provided. After receiving physiotherapy treatment 3 times, the results of the shoulder already appear symmetrical; there is an increase in the Joint Scope of Motion (LGS) of the shoulder dextra, a decrease in pain in the shoulder dextra, the loss of spasm of the anterior and medial deltoid muscles, and the ability of the patient's functional activities using the Shoulder Pain and Disability Index (SPADI). Conclusion: Physiotherapy treatment of Frozen Shoulder Dextra using InfraRed, Transcutaneous Electrical Nerve Stimulation, and Active Exercise modalities has been proven to eliminate spasms, increase joint range of motion (LGS), reduce pain, increase muscle strength and increase functional activity capabilities using Shoulder Pain and Disability Index (SPADI).